Diabetes Insipidus as a Complication of Wegener's Granulomatosis and Its Treatment with Biologic Agents. (6th July 2009) - Cunnington, Joanna Rosalind; Jois, Ramesh; Zammit, Ivan; Scott, David; Isaacs, John
Abstract : Wegener's granulomatosis of the pituitary gland resulting in diabetes insipidus is a rare complication of the disease. Standard treatment for Wegener's granulomatosis involves a combination of prednisolone and cylophosphamide, however biologic agents are now being used in refractory cases. We report three cases of patients with diabetes insipidus as a complication of Wegener's granulomatosis who were treated with biologic agents. All three cases showed clinical response to treatment with biologic agents including rituximab and alemtuzumab and two cases demonstrated improvement in pituitary gland abnormalities by MRI. Clinicians should be aware that diabetes insipidus can present as a complication of Wegener's granulomatosis and that biologic therapies may be effective in refractory cases.